Fear of Financial Investors Unjustified - Dorothea Schäfer; Alexander Fisher (Weekly Report, 2008)
In the midst of the international financial crisis, the German federal government passed the Risk Limitation Act in autumn 2007. In spring 2008 the Bundestag has finally decided on the law. The domestic private equity/buyout providers, which have not previously been subject to banking supervision, are among the main addressees of the act. Among others, "objectionable macroeconomic activities of financial investors" are to be hindered or prevented, without simultaneously "impairing efficient financial and corporate transactions". In short, the regulation of activities is intended to have a stabilizing effect in the midst of turbulent times. Private equity funds can particularly be regarded as a supplement to the traditional instruments of corporate financing. In a study recently presented by DIW Berlin, it was determined that private equity funds generally do not swarm in on German companies "like locusts". Their macroeconomic significance has so far tended to be minor. An expansion of commitment by private equity funds would be welcomed. Particularly SMEs can profit from it.
Keywords: G23; G24; G34; 330; Private equity; Leveraged buyouts; Corporate finance